Credit Rationing with Heterogeneous Borrowers in Transition Economies: Evidence from Slovakia - Pavel Ciaian (Economics and Econometrics Research Institute (EERI), 2004)
This paper investigates the macroeconomic importance of credit rationing and whether banks use characteristics such as ownership structure and institutional type of borrowers in order to regulate the risk of loaned funds. To test this, monthly data for 2000–2002, extracted from the National Bank of Slovakia monetary review, were used. The paper finds that credit rationing was not present during the period analysed, implying that the credit market can be approximated with a typical supply and demand relationship. The second finding of the paper is that intermediaries use the ownership type and institutional form of borrowers to regulate risk.
Keywords: E51; G32; P24; 330; Credit rationing; heterogeneous borrowers; transition countries